INDIVIDUAL FEATURES OF THE BOVINE COLOSTRUM PROTEOME - Ivanov , Ievgen; Kozheshkurt , Valentyn (Collection of scientific papers «ΛΌГOΣ», 2023)
One of the urgent tasks of biotechnology is obtaining of biologically active compounds of natural origin. Colostrum is a promising object for solving such problems, since it contains a large number of various natural compounds. Bovine colostrum proteins are of particular interest in this respect. As is known, most farm animals (calves, foals, piglets, camels) are born agammaglobulinemic [1] and receive passive immunity due to the first intake of colostrum, which is extremely rich not only in immunoglobulins, but also in various protein factors regulating both the immune system and the general metabolism of the body. Of great interest as factors regulating metabolism are low molecular weight fractions of proteins and peptides, which include the so-called transfer factors [2]. These are peptides with a molecular weight from 3500 Da to 6000 Da, which are inherent in all animals, are not species specific, they carry antigenic fragments and stimulate the activity of the immune system [3]. As is known, a cow gives from 5 to 10 liters of colostrum per milking, which significantly exceeds the needs of a calf [4], and the remaining amounts of colostrum can be used for industrial processing in order to obtain various biologically active compounds. Despite the fact that according to Chaudhary et.al. 2016 colostrum is “liquid gold” and has long been used in traditional medicine, it has not yet found proper use in modern industrial processing. This is due to a number of features and unresolved problems: the difficulty of storage and the peculiarity of processing; incomplete knowledge of its effect on the functional characteristics of an adult organism; instability and high individual variability of composition. A number of experts believe that the potential of biologically active compounds of colostrum, including its low molecular weight components, is not fully used [5]. In this regard, a part of the proteomic composition was studied, which includes proteins and peptides with a molecular weight from 4500 kDa to 9500 kDa, in different cows kept in the same farm, receiving the same feed, of the same breed and of the same age. To do this, fat was removed from fresh colostrum by repeated sequential centrifugation at 3000 g for 20 min, followed by casein precipitation at the isoelectric point. High molecular weight fractions of proteins were removed by membrane filtration; for this, filters with a pore diameter of 10 μm were used. The analysis of the obtained samples was carried out on a mass spectrometer Autoflex II LRF 20 “Bruker Daltonics” (Germany).